Dukungan Sosial pada Perkembangan Mental Individu - Putri Maharani; Nopal Krisna Junifa (DAWUH : Islamic Communication Journal, 2024)
This research aims to explain social support on individual mental development. According to Cobb, social support is defined as comfort, care, appreciation, or support that a person feels from other people or groups. Social support arises from the belief that there are people who are ready to help when a situation occurs that is considered to cause problems. This assistance is considered to increase positive feelings and increase self-esteem. The research method uses literature study, by analyzing 27 journals as primary data. Data analysis in several stages, the first stage is determining the theme, the second stage is selecting journal articles that are relevant to the theme and in accordance with the time limit of the last 9 years, the third stage is a review process of 7 journal articles, the fourth stage is categorization and the fifth stage is closing conclusions. The research results show that social support has an important role in several components in psychological well-being, emotional intelligence, academic adjustment, facilitating daily activities in autistic children and levels of depression. It is hoped that this research will be able to examine in more depth the theme of social support on individual mental development